Synonymy in English terminology on television - O. A. Guryanova (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the study of synonymy in English terminology on television. Different approaches to the problem of synonymy in scientific terminology are considered. The author analyzes different categories of terms-synonyms. In this paper, synonymous rows are analyzed in accordance with the length of the row. A distinctive feature of the English terminology of television is the predominance of synonymous rows with two terms in their composition. The revealed regularities of the studied terminology should be taken into account by specialists of this subject area, linguists-translators and terminographers providing the collection and processing of professionally-oriented material